"Reply" to R. G. Gregory, "A Measure of Technological Change and Returns to Scale: A Comment" - Brown, Murray; Popkin, Joel (The Review of Economics and Statistics, 1965)
Murray Brown, Joel Popkin, "Reply" to R. G. Gregory, "A Measure of Technological Change and Returns to Scale: A Comment", The Review of Economics and Statistics, Vol. 47, No. 4 (Nov., 1965), pp. 454-457